Leisure in mental health occupational therapy interventions: a qualitative investigation (Research, Society and Development, 2021)
Mental health care has been shifting from treating mental illness to health promotion. Occupational therapists aligned with the new paradigm can include leisure in their recovery-oriented interventions helping mental health patients live a meaningful and satisfactory life. The aim of this paper is to determine the common perceptions of leisure among occupational therapists who practice in mental health settings, and to understand how they implement leisure as an intervention when working with individuals with severe mental health disorders. A qualitative methodology was used to explore Occupational Therapy perceptions of leisure. Through snowball sampling 5 occupational therapists from a metropolitan city in the Midwest of the United States of America to complete a semi-structured interview were recruited. American Occupational Therapy Association Practice Framework (3rd edition) guided the thematic analysis. Three themes emerged, including Concepts of Leisure, Occupations, and Leisure as Therapy. Theme definitions, examples and implications are discussed. Although occupational therapy practitioners in mental health consider leisure important, it is underutilized in their interventions. The professional’s perspectives of leisure influences how they include it in their practice.